Embracing the complexity: Older adults with cancer-related cognitive decline—A Young International Society of Geriatric Oncology position paper. Issue 2 (March 2020) - Pergolotti, Mackenzi; Battisti, Nicolò Matteo Luca; Padgett, Lynne; Sleight, Alix G.; Abdallah, Maya; Newman, Robin; Van Dyk, Kathleen; Covington, Kelley R.; Williams, Grant R.; van den Bos, Frederiek; Pollock, YaoYao; Salerno, Elizabeth A.; et al.
Abstract: Cancer-related cognitive decline (CRCD) may have particularly significant consequences for older adults, impacting their functional and physical abilities, level of independence, ability to make decisions, treatment adherence, overall quality of life, and ultimately survival. In honor of Dr. Hurria's work we explore and examine multiple types of screening, assessment and non-pharmacologic treatments for CRCD. We then suggest future research and clinical practice questions to holistically appreciate the complexity of older adults with cancer's experiences and fully integrate the team-based approach to best serve this population.